The Effect of Fatigue on Visuospatial Perception Accuracy of Basketball Athletes - Muhammad Ivan Miftahul Aziz; Andi Sahrul Jahrir (Journal Physical Health Recreation (JPHR), 2025)
This study aims to analyze the impact of fatigue on the accuracy of visuospatial perception of basketball athletes. A total of 23 athletes from BKMF Basketball FIKK UNM participated in this study, using a pre-test and post-test quasi-experiment design. Visuospatial perception was measured with the Mental Rotation Test (MRT) before and after a high-intensity exercise program designed to induce physical fatigue. The results showed a significant decrease in perceptual accuracy (pre-test: 82.09%; post-test: 68.43%) as well as an increase in response time (pre-test: 6.81 minutes; post-test: 7.78 minutes) (p < 0.001). These findings indicate that physical fatigue can impair athletes' ability to process, interpret and make decisions based on visual information. This impact could potentially reduce technical and tactical performance during matches. The implications of this study highlight the importance of integrating cognitive training alongside physical training to maintain athletes' cognitive performance under fatigue conditions.